Group Controllability of Discrete-Time Time-Delayed Multiagent Systems with Multiple Leaders - Bo Liu; Qing An; Licheng Wu; Rong Li; Housheng Su; Yue Han (Complexity)
The group controllability is a unique distinct perspective and a further generalization of the controllability problem of discrete-time time-delayed multiagent systems (MASs) with multiple leaders. The group controllability concept of discrete-time time-delayed MASs with multiple leaders is proposed, its equivalent augmented system without time delay is reformulated, and the group controllability criteria are obtained in this paper. Numerical simulations are presented finally.